Genetic diversity and relationship of husk tomato (Physalis spp.) from East Java Province revealed by SSR markers - halimatus sadiyah; Sumeru Ashari; Budi Waluyo; andy Soegianto (Society for Indonesian Biodiversity, 2021)
Abstract. Sadiyah H, Ashari S, Waluyo B, Soegianto A. 2021. Genetic diversity and relationship of husk tomato (Physalis spp.) from East Java Province revealed by SSR markers. Biodiversitas 22: 184-192. This study aimed to investigate the genetic diversity and relationship of Physalis spp. from East Java province, Indonesia. A total of the 33 Physalis accessions was analyzed employing 16 SSR markers. AMOVA, UPGMA clustering, and non-parametric ANOVA analyses were applied. The results showed Genetic diversity in this sample showed lower levels (He =0.171), as compared to other studies of Physalis that used different molecular markers. The dendrogram revealed the presence of five groups, the different species belong to different small groups. The two major groups consist of accessions originated from eastern Java and Madura Island, indicating that there is no significant difference between accessions from both areas although there is geographic isolation in the form of the strait. It is consistent with the low population differentiation and high genetic drift. The AMOVA revealed that 96% of the total variation came from the within-population (among accession), reflect that the accessions used in this study have high variation and valuable for plant improvement through breeding programs. It is recommended that future evaluation studies include more accession from minor accessions detected in the sample of this study to better represent the genetic diversity available in this crop.